Measuring Sponsorship Transparency in the Age of Native Advertising. Issue 1 (26th January 2017) - Wojdynski, Bartosz W.; Evans, Nathaniel J.; Hoy, Mariea Grubbs
Abstract : As advertisers continue to develop new formats of online content that blurs the line between advertising and news or entertainment, the need to understand how consumers process covert advertising grows. While regulators and industry practitioners agree that transparency is paramount to preventing consumer deception, there exists no established way of determining the extent to which a given message transparently conveys to consumers that is a paid advertisement. The current study makes the case for, develops, and validates a scale to measure sponsorship transparency. Following traditional scale development methods, the study generates a pool of items based on consumer and expert input, reduces the number of items based on empirical research, and evaluates scale validity and reliability using a diverse national sample.